Can performance in biathlon world cup be predicted by performance analysis of biathlon IBU cup? - Dzhilkibaeva, N.; Ahrens, M.; Laaksonen, M. S. (International Journal of Performance Analysis in Sport, 2019)
Biathlon performance consists of skiing speed, shooting accuracy (ShAcc) and shooting time (ShT). For coaches, the evaluation of the performance level of biathletes to select biathletes to particular competitions is crucial. The present study aimed to compare two different approaches to analyse biathletes` skiing performance (relative skiing speed, SS%, and skiing time coefficient, STC), and to analyse the relationship between different parameters of performance between two competition levels (World Cup, WC and IBU Cup, IC). The data from four competitive seasons were analysed including 166 male and 184 female biathletes. The correlation between SS% in IC and WC was similar for both sexes (males r = .81; females r = .78) compared to correlation between STC in IC and WC (males r = .80; females r = .75) (p < .001), whereas the mean absolute percentage error was higher for STC (1.2% and 1.8% vs. 18% and 22%). SS%, ShAcc and ShT in IC explained 54% and 45% (p < .001) of the entire WC rank for males and females, respectively. Thus, SS% is recommended to be used for evaluation of biathletes` skiing performance. To predict the performance in WC from results in IC should be used with caution.